2018
DOI: 10.1038/s41467-018-07825-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immune surveillance accelerates accumulation of senescent cells and aging

Abstract: Cellular senescence is a stress response that imposes stable cell-cycle arrest in damaged cells, preventing their propagation in tissues. However, senescent cells accumulate in tissues in advanced age, where they might promote tissue degeneration and malignant transformation. The extent of immune-system involvement in regulating age-related accumulation of senescent cells, and its consequences, are unknown. Here we show that Prf1−/− mice with impaired cell cytotoxicity exhibit both higher senescent-cell tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
325
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(340 citation statements)
references
References 70 publications
6
325
0
9
Order By: Relevance
“…It will be interesting to determine if senolytic-treatment can also improve such cases of severe damage. Indeed, senolytics have already been shown to function in the liver of mouse models with immune dysfunction (Ovadya et al, 2018), and in ameliorating age-related hepatic steatosis (Ogrodnik et al, 2017). Interestingly, as PH is associated with induction of steatosis in older animals as shown here and elsewhere (Loforese et al, 2017), our study further supports that these drugs could aid in liver regeneration in elderly patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It will be interesting to determine if senolytic-treatment can also improve such cases of severe damage. Indeed, senolytics have already been shown to function in the liver of mouse models with immune dysfunction (Ovadya et al, 2018), and in ameliorating age-related hepatic steatosis (Ogrodnik et al, 2017). Interestingly, as PH is associated with induction of steatosis in older animals as shown here and elsewhere (Loforese et al, 2017), our study further supports that these drugs could aid in liver regeneration in elderly patients.…”
Section: Discussionsupporting
confidence: 82%
“…on 2 consecutive days immediately before PH with DMSO (2%) or ABT-737 (25 mg/kg body weight; AdooQ Bioscience). DMSO and ABT-737 were prepared in the following working solution: 30% propylene glycol, 5% Tween 80, 5% dextrose in water (pH 4-5) as previously reported (Ovadya et al, 2018).…”
Section: Elimination Of Senescent Cells In Vivomentioning
confidence: 99%
“…Under physiological conditions, senescence eliminates damaged cells and is involved in tissue restoration on acute stress or injury. The secretion of chemokines and cytokines such as IL‐1b, IL‐8, and MCP‐1 through SASP attracts immune cells, leading to immunological clearance of the senescent cells . Consistently, aging and chronic stress induce telomere attrition and excessive SASP, leading to accumulation of senescent cells and insufficient tissue regeneration .…”
Section: Senescence In Health and Diseasementioning
confidence: 99%
“…The secretion of chemokines and cytokines such as IL-1b, IL-8, and MCP-1 through SASP attracts immune cells, leading to immunological clearance of the senescent cells. (14,15) Consistently, aging and chronic stress induce telomere attrition and excessive SASP, leading to accumulation of senescent cells and insufficient tissue regeneration. (14,16) Concurrently, hematopoietic stem cells decrease with age, resulting in fewer immune cells and a decline in the immune response, provoking a vicious cycle of defective clearance of senescent cells.…”
Section: Senescence In Health and Disease General Aspectsmentioning
confidence: 99%
“…In addition, studies have indicated that the activation of pathways, downstream of the DNA damage response (DDR), accelerate the process of aging . On the other end, elimination of senescent cells in mice displaying premature aging due to genomic instability increases animal life span, and elimination of senescent cells in wild‐type mice increases their health span . Moreover, supporting further the causal relationship between accumulation of senescent cells and the aging phenotype, it was shown that elimination of p16 Ink4a ‐positive senescent cells decreased the onset of age‐related pathologies in both progeroid and wild‐type mice .…”
Section: Organismal Aging and Cellular Senescencementioning
confidence: 77%